ESTIMATION OF THE OPTIMUM SIZE OF PLOTS FOR SOYBEAN RADIOMETER EXPERIMENTS - MICHELS, Roger Nabeyama; CANTERI, Marcelo Giovanetti; AGUIAR E SILVA, Marcelo Augusto de; BERTOZZI, Janksyn; DAL BOSCO, Tatiane Cristina (Brazilian Journal of Biometrics, 2021)
The lack of error of experimental planning in agricultural field studies can result in rework, causing the waste of financial resources. The determination of the optimal size of the experimental plot for carrying out the treatments can minimize these problems. The objective of this paper was to estimate the optimal plot size for measuring reflectance in soybeans, without treatment, using the modified maximum curvature method and the maximum distance method. Reflectance readings were taken in the soybean crop with the aid of the GreenSeeker® equipment, in basic experimental units of 0.45 m², in an area of 7 lines and 8 meters in length. The data were collected in three phenological stages of soy (R4, R5.5 and R6), obtaining 63 simulations of experimental area in each stage. Based on the results, it is recommended to use plots of 7.20 m², with grouping of 4 lines of 4 m in length.